Word Bank: Learning Media on Poetry Writing Materials for Fourth Grade of Elementary School - Alfianita Ayu Larasati; Ali Mustadi (Jurnal Ilmiah Sekolah Dasar, 2024)
Students benefit from writing poetry because they can express their feelings at the time through beautiful words in the form of poetry. Writing poetry in learning can be packaged using learning media. Learning media is extremely beneficial to the learning process. Students will understand the material provided by the teacher more easily if they use learning media. Therefore, this research aims to produce the learning media product "Word Bank" to improve the ability to write poetry in fourth grade elementary school. This study applied the Hannafin and Peck model of Research and Development. In this study, 15 students of IV grade were used as research subjects. Observation, interviews, questionnaires, and documentation were used as research instruments. Interactive analysis techniques and presentations were used in data analysis techniques. According to the research findings, “Word Bank” learning media has a “very high” feasibility level. The results of the initial trial, which was conducted on 5 students, were classified as “very high” based on the acquisition of the two scores obtained. Students’ pretest and post-test scores in the experimental class showed a t-count of -8.817 with df 18 and Sig. (2-tailed) of 0.000. Thus, the results of the t-test for the pretest and post-test values of the experimental class show that the value of Sig. (2-tailed) 0.000 < 0.05 (5%). Can be concluded that there is a significant difference in ability wrote poetry.